2020
DOI: 10.3390/w12020339
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Land-Use on the Hierarchical Pore Size Distribution and Water Retention Properties in Loamy Soils

Abstract: Soil hydraulic properties are very sensitive to land-use in regions susceptible to physical degradation. Intensive agricultural practices often lead to soil compaction and erosion in the investigated area. The main goal of this paper was to evaluate the impact of land-use on the pore size distribution and water retention in loamy soils. The soil water retention curve (SWRC) combined the total porosity and the water retention of the undisturbed sample at 3, 10, 31, 100, 310, and 1000 hPa suctions and the distur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 56 publications
2
14
1
Order By: Relevance
“…Authors added that pore creation could result from different mechanisms involving: i) shrinking and swelling of soil and organic particles as a response to wetting and drying cycles ii) decomposition of organic matter by microorganisms, iii) fungal hyphae creation that pushing aside silt-sized particles. Similar findings were also obtained by Dlapa et al [28], who reported that a higher carbon content promotes the formation of elongated pores with a characteristic pore diameter of 15-27 μm. Authors added that creation of micro-crack improves soil hydraulic properties due to the higher ability of structural pores to drain water during the rainfall.…”
Section: Environmental Effect Of Exogenous Organic Matter On Pore Sizsupporting
confidence: 90%
See 2 more Smart Citations
“…Authors added that pore creation could result from different mechanisms involving: i) shrinking and swelling of soil and organic particles as a response to wetting and drying cycles ii) decomposition of organic matter by microorganisms, iii) fungal hyphae creation that pushing aside silt-sized particles. Similar findings were also obtained by Dlapa et al [28], who reported that a higher carbon content promotes the formation of elongated pores with a characteristic pore diameter of 15-27 μm. Authors added that creation of micro-crack improves soil hydraulic properties due to the higher ability of structural pores to drain water during the rainfall.…”
Section: Environmental Effect Of Exogenous Organic Matter On Pore Sizsupporting
confidence: 90%
“…In contrast, textural porosity refers to pores within aggregates and between primary soil particles. These kinds of structures are also known as matrix, intra-aggregate, and inter-particle pores [28].…”
Section: Environmental Effect Of Exogenous Organic Matter On Pore Sizmentioning
confidence: 99%
See 1 more Smart Citation
“…Compaction obviously results in an overall reduction of the total porosity (Φ), but more importantly, it results in a shift in the pore-size distribution with a reduction of the macroporosity (D ϕ > 30 μm, pore diameter D ϕ ) and an increase in micro-porosity (D ϕ < 6 μm) (Lipiec et al, 2012). Dörner et al (2016) and Dlapa et al (2020) showed that LU and LU change had significant negative effects on the water-retention and air-phase characteristics in terms of soil-aeration processes.…”
Section: Introductionmentioning
confidence: 99%
“…Research in Slovakia has mostly focused on the forest as a complex system, which retains water (Čaboun and Minďáš 2003, Holko et al 2009and Čaboun et al 2010. Several authors have also studied the influence of the OHFS on SWR (Heiskanen and Makitalo 2002, Greiffenhagen et al 2006, Li et al 2014, Gomyo and Kuraji 2016, Hlaváčiková et al 2016, Zvala et al 2018, Dlapa et al 2020and Zhu et al 2020.…”
Section: Introductionmentioning
confidence: 99%